2010
DOI: 10.1016/j.mcn.2009.11.004
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1-induced amyloid beta accumulation in brain endothelial cells is attenuated by simvastatin

Abstract: HIV-1-infected brains are characterized by increased amyloid deposition. To study the influence of HIV-1 on amyloid beta (Aβ) homeostasis at the blood-brain barrier (BBB) level, we employed a model of brain microvascular endothelial cells exposed to HIV-1 in the presence or absence of Aβ. HIV-1 markedly increased endogenous Aβ levels and elevated accumulation of exogenous Aβ. Simvastatin, the HMG-CoA reductase inhibitor, blocked these effects. We next evaluated the effects of HIV-1 and/or simvastatin on expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
66
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 48 publications
(69 citation statements)
references
References 41 publications
2
66
1
Order By: Relevance
“…Indeed, brain vascular dysfunction and the blood-brain barrier (BBB) are critical in Aβ accumulation in the brain (7). Observations from our laboratories have shown that exposure to HIV results in enhanced Aβ levels in human brain microvascular endothelial cells (HBMEC) and increased transendothelial transfer (8,9), supporting the hypothesis that brain endothelial cells may contribute to brain Aβ accumulation in HIV infection.…”
Section: Introductionsupporting
confidence: 57%
“…Indeed, brain vascular dysfunction and the blood-brain barrier (BBB) are critical in Aβ accumulation in the brain (7). Observations from our laboratories have shown that exposure to HIV results in enhanced Aβ levels in human brain microvascular endothelial cells (HBMEC) and increased transendothelial transfer (8,9), supporting the hypothesis that brain endothelial cells may contribute to brain Aβ accumulation in HIV infection.…”
Section: Introductionsupporting
confidence: 57%
“…HIV-1 is known to increase Aβ accumulation and transfer across HBMEC (Andras et al, 2010, 2012); therefore, we evaluated the impact of HIV-1 on Aβ levels in ECV produced by these cells. For these experiments, HBMEC were exposed to HIV-1 (30 ng/ml) and/or 100 nM Aβ (1–40) HiLyte for 48 h, and Aβ (1–40) HiLyte fluorescence was visualized in ECV isolated from cell culture media.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, the blood-brain barrier (BBB) is crucial for Aβ homeostasis, and plays a role in Aβ accumulation in the brain (Deane and Zlokovic 2007). To support this notion, we demonstrated that HIV-1 could elevate Aβ levels in human brain endothelial cells (HBMEC), and enhance its transendothelial transfer (Andras et al 2010, Andras et al 2012). …”
Section: Introductionmentioning
confidence: 92%
“…Throughout the study, HBMEC were exposed to HIV-1 particles for 24 h at the p24 level of 30 ng/ml. This type of exposure was shown to be highly effective in stimulation of cellular Aβ levels [12]. Plasma levels of p24 were reported to reach ~5–6 log 10 fg p24/ml in non-treated HIV-1-infected patients, which correspond to ~0.1-1 ng p24/ml [19].…”
Section: Methodsmentioning
confidence: 99%
“…Important observations from our laboratories indicate that exposure to HIV-1 results in enhanced Aβ levels in human brain endothelial cells (HBMEC) and increased its transendothelial transfer [12, 13], suggesting that brain endothelial cells contribute to accumulation of Aβ in HIV-1-infected brains. These observations are consistent with the evidence that brain vascular dysfunction and the blood brain barrier (BBB) are playing important roles in amyloid pathology observed in AD [14].…”
Section: Introductionmentioning
confidence: 99%